SOIL AMENDMENT WITH COAL DUST AND ITS CONDITIONING: IMPACT ON FERTILITY STATUS AND ITS PRODUCTIVITY - Meshram, Prafulanand N.; Gudadhe, Swapnil K.; Sakhare, Purushottam R. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Soil amendment with coal dust in different proportions may play an important role in the soil matrix. Particles spread on land in the mining areas, during transportation on road sides, and coal dust during pulverization and storage (coal stack yard). Coal dust particles, therefore, necessitate the need for knowing the impact/effect on the soil matrix and its ultimate effect on the fertility status and productivity of the soil. Amendment through soil conditioning with the use of micro-organisms within the soil matrix using natural biological activity may be an important factor in the soil matrix on the fertility status and productivity of the soil. Moreover, it will be a viable treatment option for the remediation of coal particle-contaminated soils or the use of coal-dust-amended soil for the reclamation of waste land in a cost-effective manner with a minimum threat to the soil. The mixed microbial consortium present in the soil was used to accelerate the conditioning of the soil. This culture of microbial consortia, along with nutrients, acts in various in situ conditions of coal-contaminated soil to help remove heavy metals present in coal, as well as different organic compounds in the soil, and serves as a manure for plant growth. In the present study, pot experiments were conducted for the germination of different plants by amending coal dust particles with soil. It was observed that the soil remediation with coal dust particles is extremely useful tool for improving the quality of poor wasteland soil without the use of fertilizer because of the conversion of hydrocarbons present in coal dust into manure with the help of soil micro flora which helps for the growth of plants. The soil quality was found to be improved after remediation with respect to cation exchange capacity (CEC) and organic matter content. There was no degradation found in soil quality after germination and frequent use under control conditions will help for the next crop growth. The present study reflects that the coal dust particles amended soil or wasteland soil not only helps to increase the productivity of soil but also the ultimate use of the coal dust particles in soil also creates to cleanup existing soil contamination and help to restore soil quality in a cost effective manner.